Pengembangan Sistem Internet Of Things (IoT) Untuk Pengendalian Suhu dan Kelembaban Sarang Burung Walet Dengan Penyiram Air Otomatis - Muhammad Naufal Raihan; Abd. Hallim; Arbansyah Arbansyah (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
This study focuses on the design and implementation of an Internet of Things (IoT)-based automated system for controlling temperature and humidity in swallow houses. The object of the study is a prototype swallow house that functions to simulate the natural environmental conditions in swallow breeding buildings. The main problem in this research is the instability of temperature and humidity, which affects the comfort and productivity of swiftlets, as well as the management process, which is still carried out manually and inefficiently. The purpose of this research is to design a system that can monitor and control temperature and humidity automatically and in real-time to create an ideal environment for swiftlets. This system uses a DS18B20 temperature sensor and a DHT22 humidity sensor connected to an ESP32 microcontroller and controlled through a web-based interface. In addition, the system is equipped with a DFPlayer Mini module to play swallow call sounds and a notification feature through the Telegram application. Test results show that the system can respond accurately to changes in temperature and humidity, perform automatic watering when conditions are not ideal, and play swift sounds according to a schedule. The system also successfully displays data in real-time and sends notifications to users. In conclusion, this system has proven effective in automating swift house environment management, improving efficiency, and has the potential to increase swift nest production.